Stimulasi Perkembangan Motorik Kasar Anak Melalui Ragam Main Melompat Di RA Assalafiyah Cirebon - An’imatun Musa’adah; Ulfah Amini; Taufiqurrahman Taufiqurrahman (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2023)
Gross motor development is a development related to the ability to use large muscles. This can be seen in the development of children's gross motor skills which are still lacking in the activities they do, one of which is jumping with variations of spinning, jumping with variations of running and jumping with variations of jumping, this game maintains body balance when playing the game of jumping and carrying flowers. The aim to be achieved in this research is to find out whether jumping with flowers can improve the gross motor skills of young children in group A at RA Assalafiyah Jatirenggang, Cirebon Regency. The research approach used is classroom action research with a qualitative research type. This research uses a research design based on the Kemmis and McTaggart model which is composed of four stages. This research is classroom action research using a model consisting of 2 cycles focused on children's gross motor development activities with a total of 15 students. The results of the research show that the game of jumping and carrying flowers with variations of spinning, jumping and running can improve children's gross motor skills. Students who were able to jump in the Pre-Cycle were 29%, 53% in Cycle 1 and 84% in Cycle II.